Evaluating Complex Problem-Solving Test Instrument Quality in Measuring Computational Thinking Skills in Global Warming: Rasch Model Analysis - Farika Nurfalah; Judhistira Aria Utama; Muslim Muslim (Jurnal Pemberdayaan Masyarakat, 2025)
This research aims to develop and evaluate a high-quality Complex Problem Solving (CPS) test instrument based on global warming issues to assess students' Computational Thinking (CT) skills. Global warming was chosen because of its contextual relevance in 21st-century education and its potential to promote higher-order thinking. The instrument consists of six essay questions that require students to demonstrate complex problem-solving skills, including decomposition, pattern recognition, abstraction, and algorithmic thinking. The method used in this study is Research and Development (RD), which contains five stages: (1) analysis of needs, (2) development of the instrument, (3) validation by an expert, (4) trial instruments, and (5) data analysis using the Rasch Model. This instrument was evaluated using the Rasch model to examine the validity, reliability, and difficulty level of its items, which were analyzed using the Minister 3.80.1 software. The results showed that the instrument achieved the "very valid" categories for content and construct validity. The raw variance explained by the measure was 76.20%, classified as "specific," indicating strong empirical validity. The Cronbach's alpha (KR-20) value was 0.91, indicating the instrument's high reliability. The item reliability value was 0.94, and the person reliability was 0.89. This means that students' consistency in answering questions was good, and the instrument had high reliability. The distribution of item difficulty levels was balanced, allowing students to be distinguished by their abilities at various levels. It can be concluded that this instrument is reliable and valid. Thus, this instrument can measure students' computational thinking skills on global warming.